Reproductive disorders of cows in several villages of Kedamean district, Gresik regency, East Java, Indonesia in 2023 - Utomo, Budi; Rimayanti, Rimayanti; Restiadi, Tjuk Imam; Amrullah, Muhammad Fajar (Universitas Airlangga, 2024)
Reproductive disorders are the main cause of economic losses in beef herds. This study aimed to determine the type of reproductive disorder in beef cows in Kedamean district, Gresik regency, related to feeding, age, and parity. The method used for this study was a survey. Primary data was obtained from field surveys by interviewing farmers, animal health officials, inseminators, and direct inspection of cows and pens. Secondary data was obtained from the Gresik Animal Husbandry and Animal Health Service. The data obtained was then compiled and performed descriptively. The results showed that the number of productive cows in this study area was 935, of which 340 (36.36%) had reproductive disorders. The highest type of reproductive disorder was ovarian hypofunction (OHF) (14.55%, 136/935) and the smallest was cystic ovaries (0.11%, 1/935). Cows aged two and three years (heifers and first parity) have a percentage of reproductive disorders of more than 60% compared to cows of other ages, most of them (13.82% and 12.65%) were OHF. The cows fed straw have a greater percentage of reproductive disorders than cows fed field grass. Cases of OHF engaged the first position followed by cases of silent estrus and persistent corpus luteum. It could be concluded that reproductive disorders in the form of OHF, persistent corpus luteum, and silent estrus in several villages in Kedamean district, Gresik regency, East Java, Indonesia in 2023 mostly occured at the age of two to three years on heifers or first parity, fed straw.